Violence against women: a study on nature, prevalence and extent - Vachhani, Pushti V.; Bhimani, Nishant R.; Sutaria, Nishith B.; Purani, Shyamal K.; Kartha, Girija P. (International Journal of Research in Medical Sciences, 2017)
Background: To study the nature, prevalence and extent of domestic violence against women in the study area. Methods: The cross-sectional study was carried out in the urban and rural area of Surendranagar district of Gujarat. Total 600 ever married women of 15-49 years of age were selected for the study purpose. The self-administered questionnaire was used to gather all the information. Steps were taken up to maintain confidentiality. Results: Out of total 600 women, 231 (38.5%) were victims of domestic violence in one form or the other. The analysis based on each form of violence discloses that about 83% were victims of psychological violence, about 54% of the victims had experienced physical violence, about 32% were victims of economical violence and about 24% were victims of sexual violence. Conclusions: Husband was the frequent instigator of domestic violence. Psychological violence is the commonest form of violence experienced by the victims.